Modernism’s Zoo (Pet and Pen in Virginia Woolf’s Flush) - Frédéric Regard (Sillages Critiques)
This article plays on the two possible senses of the word “renaissance,” which suggests both the fact of being born again, and that period in European history of an artistic revival, achieved under the influence of classical models. The paper begins with registering the renewal of critical interest in Virginia Woolf’s Flush, a fictional biography of Elizabeth Barrett Browning’s dog. Its aim, however, is to go beyond the Deleuzian approach that seems to have prevailed so far, according to which Flush is a narrative of the becoming-animal of the artist. The central argument here is that Woolf’s narrative gesture in fact remains profoundly human even as it is paradoxically threatened by its own animality from within. By going back to the fundamental categories of Aristotelian philosophy and supporting his argument with detailed narratological analyses of the narrative, the author suggests that this canine biography should be read, precisely, not as an auto/biography – where the anthropological machine would still be running at full speed – but as a fable of the Modernist artist’s discovery of her own linguistic infancy. This study is much indebted to the works of Hannah Arendt and Giorgio Agamben, the twentieth century’s most eminent Aristotelian philosophers, but it also draws on Donna Haraway’s proposal of a necessary “reinvention of nature.” Still, the core argument finds its inspiration in Jacques Derrida’s “deconstruction” of the primacy of voice (phone) over the written sign (gramma).